A Comparison Between AH 26 and Sealapex for Post-Obturation Pain - Ahmad Rana, Muzzamil Jamil; Rana, Mehmood Ahmad; Alam, Mafaza; Bangash, Ajmal Yousaf; Bhangar, Faisal; Munir, Asma (Pakistan Armed Forces Medical Journal, 2022)
Objective: To find out the post-obturation pain with Sealapex and AH26 Sealers on the first, third and seventh day.Study Design: Quasi-experimental study.Place and Duration of Study: Armed Forces Institute of Dentistry, Rawalpindi Pakistan, from May to Nov 2019.Methodology: Three hundred eighty-eight patients of either gender, ranging from age 20 to 45, presenting in the OPD for root canal treatment were selected. Teeth were opened, cleaned and shaped properly with rotary HyFlex EDM files. Obturation was done with Sealapex sealer in half cases, and the rest were obturated using AH26. Post-operative pain was recorded with VAS scoring on the days 1,3 and 7.Results: Of 388 patients reporting, 131(67.5%) were males, and 63(32.5%) were females. Comparative pain recording on the days 1, 3 and 7 showed post-operative pain for the AH Sealer-Group as 80(58%), 64(72.3%), 22(84.3%) and Sealapex SealerGroup as 58(42%), 24(27.7%) and 4(15.7%) respectively. The difference between post-obturation pain of both groups on all days was statistically significant, with an increased pain in the AH 26 Sealer-Group. There was a statistically significant relation between post-operative pain with gender distribution. Younger patients reported more pain as compared to older subjects.Conclusion: The post-obturation pain for AH26 is more than Sealapex sealer which gradually decreases with each passing day.